The physics of planet earth and its natural wonders - Livanov, Dmitry (Springer, 2023)
From earthquakes to the northern lights and tsunamis to glacier movement, the author explains thousands of phenomena in the world around us. All of this is done using language that is simple and understandable, and at the same time this book does not try to deceive the reader, as materials of this nature often do, but uses exact physical formulas where they are needed.